Indonesia’s Youth Unemployment Rate: Evidence from Sakernas Data - Sitompul, Natasha Karina; Athoillah, Moh. (AIBPM Publisher, 2023)
Unemployment is a problem that is often faced by every country, including Indonesia. The phenomenon of unemployment in Indonesia shows that a highly educated population does not necessarily have a job, especially in the young age group. This study aims to determine the factors that affect young educated unemployment in Indonesia. This study used variable levels of education, training, experience, major of education, gender, geographical area and urban/rural classification. Using the National Labour Force Survey (SAKERNAS) 2019, provided by Central Statistical Agency, this research employs a logistic regression model. The results showed that 50.99% of the young educated people in Indonesia did not have a job. All variables in this study have a significant effect on young educated unemployment in Indonesia. The quality of education needs to be improved so that the competitiveness of the Indonesian workforce increases, and self-development programs can help reduce the youth-educated unemployment rate.